Impact of the citizen science project COLLECT on ocean literacy and well-being within a north/west African and south-east Asian context - Severin, Marine I.; Akpetou, Lazare Kouame; Annasawmy, Pavanee; Asuquo, Francis Emile; Beckman, Fiona; Benomar, Mostapha; Jaya-Ram, Annette; Malouli, Mohammed; Mees, Jan; Monteiro, Ivanice; Ndwiga, Joey; Neves Silva, Péricles; et al. (Frontiers in Psychology, 2023)
Plastic pollution is both a societal and environmental problem and citizen science has shown to be a useful tool to engage both the public and professionals in addressing it. However, knowledge on the educational and behavioral impacts of citizen science projects focusing on marine litter remains limited. Our preregistered study investigates the impact of the citizen science project Citizen Observation of Local Litter in coastal ECosysTems (COLLECT) on the participants’ ocean literacy, pro-environmental intentions and attitudes, well-being, and nature connectedness, using a pretest-posttest design. A total of 410 secondary school students from seven countries, in Africa (Benin, Cabo Verde, Côte d’Ivoire, Ghana, Morocco, Nigeria) and Asia (Malaysia) were trained to sample plastics on sandy beaches and to analyze their collection in the classroom. Non-parametric statistical tests (n = 239 matched participants) demonstrate that the COLLECT project positively impacted ocean literacy (i.e., awareness and knowledge of marine litter, self-reported litter-reducing behaviors, attitudes towards beach litter removal). The COLLECT project also led to higher pro-environmental behavioral intentions for students in Benin and Ghana (implying a positive spillover effect) and higher well-being and nature connectedness for students in Benin. Results are interpreted in consideration of a high baseline in awareness and attitudes towards marine litter, a low internal consistency of pro-environmental attitudes, the cultural context of the participating countries, and the unique settings of the project’s implementation. Our study highlights the benefits and challenges of understanding how citizen science impacts the perceptions and behaviors towards marine litter in youth from the respective regions.